You are on page 1of 9

1

[a, b]

f (xi )xi

(1)

i=1

lim

f (xi )xi

(2)

i=1

b
f (x)dx
a

(3)

Analogy

xi f (xi )xi

i=1

1 xi f (xi )
xi xi

lim

xi f (xi )xi

i=1

x f (x)dx
a

y = f (x) 1
1

x i

i=1

[a, b] b a
b
dx = b a

(4)

2
dx x dx b a
b a

S
s1
S=
ds

(5)

s0

4 x dx x
b ads diential
arc
5
5
ds dx
x
x = 1 x = 10
x = 1 x = 10
1

g(x) = x f (x) y = g(x)

f (x)
2
1

s1

S=

ds
s0

ds

ds
ds dx
x y

ds =

dx2 + dy2

dx

ds =

dy
1+
dx

)2
dx

y = f (x) x = a x = b

( )2
x=b
b
dy
S=
ds =
1+
dx
dx
x=a
a

y = x 2 x = 1 x = 4

dy 3 1
= x2
dx 2

3 1
1 + x2
2

)2

dx =
1

9
1 + x dx
4

9
u = 1 + x
4

y =

ex + ex
x = 0 x = ln(3)
2

dy ex ex
=
dx
2
5

ln(3)
0
ln(3)

ex ex
1+
2
1+

ln(3)

=
ln(3)

)2
dx

e2x 2 + e2x
dx
4

e2x + 2 + e2x
dx
4
(
)
ex + ex 2
dx
2

ex + ex
dx
2
0

ex ex ln(3) 3

=
=
2 0
2
ln(3)

1
3

dy 2 1
2
y = x 3
= x 3 x = 1 x = 8
dx 3
8
4 2
1 + x 3 dx
9
1
2 1
x 3 = tan()
3

ds =
dx

dx2 + dy2

ds =

dy
1+
dx

)2
dx

dy

( )2
dx
ds =
+ 1 dy
dy
6

y y = x 3
3

x = y 2 x = 1 y = 1 x = 8 y = 4

4
1

3 1
1 + y2
2

)2
dy

x = g(y) y = c y = d

( )2
y=d
d
dx
S=
ds =
1+
dy
dy
y=c
c

y = f (x) or x = g(y) x = ay = c x = by = d

S=
a

=
c

)2
dy
dx
1+
dx

( )2
dx
1+
dy
dy
(

x = ln(sec(y)) y = 0 y =

x = g(y) y

dx
= tan(y)
dy
7

1 + tan2 (y) dy

sec2 (y) dy

sec(y) dy
0


) 3
= ln sec(y) + tan(y)

0

= ln( 2 + 3 )
(

y
dt

ds = dx2 + dy2 =

dx
dt

)2

dy
+
dt

)2
dt

)2
dy
S=
1+
dx
dx
a

( )2
d
dx
1+
dy
=
dy
c

t 2 ( )2 ( )2
dy
dx
=
+
dt
dt
dt
t1

ds =

dx2 + dy2

x = r cos(t),y = r sin(t)
dx
= r sin(t)
dt
dy
= r cos(t)
dt

r2 sin2 (t) + r2 cos2 (t) dt

0
2

r2 dt

0
2

r dt = 2r

=
0

x y